Brief Report: Recent Infection, Sexually Transmitted Infections, and Transmission Clusters Frequently Observed Among Persons Newly Diagnosed With HIV in San Francisco. (15th August 2015) - Truong, Hong-Ha M.; Pipkin, Sharon; O'Keefe, Kara J.; Louie, Brian; Liegler, Teri; McFarland, Willi; Grant, Robert M.; Bernstein, Kyle; Scheer, Susan
Abstract : Abstract: There were 1311 newly diagnosed HIV cases in San Francisco between 2005 and 2011 that were linked to care at publicly funded facilities and had viral sequences available for analysis. Of the 214 cases characterized as recently infected with HIV at the time of diagnosis, 25% had a recent sexually transmitted infection diagnosis (vs. 10% among longer-standing HIV infections, P < 0.001) and 57% were part of a phylogenetic transmission cluster (vs. 42% among longer-standing HIV infection, P < 0.001). The association observed between recent HIV infection and having a sexually transmitted infection diagnosis during the interval overlapping likely HIV acquisition points to potential opportunities to interrupt HIV transmission.